2020
DOI: 10.9734/ejnfs/2020/v12i730253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginger and Cinnamon on the Proximate Composition and Sensory Properties of Corn Ogi

Abstract: Objective: Ogi is a fermented cereal gruel produced from maize, sorghum or millet. The objective of the study was to investigate the effect of ginger and cinnamon on the proximate composition and sensory properties of corn ogi. Methodology: Ogi slurry was prepared from corn and fortified with 5% ginger, 5% cinnamon, 5% ginger: 5% cinnamon and 2.5% ginger: 2.5% cinnamon spices and 100% corn ogi as control. The samples were analyzed for proximate composition and sensory properties using standard methods.&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The protein, fat, and carbohydrate compositions of the ogi contributed to the overall energy value of the samples (Atwater factor). The energy values obtained from this study align closely with those previously reported by Emelike et al (2020) for ogi spiced with ginger and cinnamon (387.77-391.98 kcal). Values are Mean±standard deviation.…”
Section: Proximate Composition Of Maize Ogi Samples With the Inclusio...supporting
confidence: 90%
See 3 more Smart Citations
“…The protein, fat, and carbohydrate compositions of the ogi contributed to the overall energy value of the samples (Atwater factor). The energy values obtained from this study align closely with those previously reported by Emelike et al (2020) for ogi spiced with ginger and cinnamon (387.77-391.98 kcal). Values are Mean±standard deviation.…”
Section: Proximate Composition Of Maize Ogi Samples With the Inclusio...supporting
confidence: 90%
“…Carbohydrate content was determined by the difference: 100% -(% MC + % Ash + % Crude protein + % Fat + % Crude fibre). The energy content (E) was calculated using Atwater factor method as described by Emelike et al (2020).…”
Section: Proximate Analysesmentioning
confidence: 99%
See 2 more Smart Citations